Bt Resistance Implications for Helicoverpa zea (Lepidoptera: Noctuidae) Insecticide Resistance Management in the United States. Issue 6 (2nd October 2018) - Reisig, Dominic D; Kurtz, Ryan
Abstract: Both maize and cotton genetically engineered to express Bt toxins are widely planted and important pest management tools in the United States. Recently, Helicoverpa zea (Boddie) (Lepidoptera: Noctuidae) has developed resistance to two toxin Bt maize and cotton (Cry1A and Cry2A). Hence, growers are transitioning to three toxin Bt cotton and maize that express both Cry toxins and the Vip3Aa toxin. H. zea susceptibility to Vip3Aa is threatened by 1) a lack of availability of non-Bt refuge crop hosts, including a 1–5% annual decline in the number of non-Bt maize hybrids being marketed; 2) the ineffectiveness of three toxin cultivars to function as pyramids in some regions, with resistance to two out of three toxins in the pyramid; and 3) the lack of a high dose Vip3Aa event in cotton and maize. We propose that data should be collected on current Cry-resistant H. zea in the field to inform future Bt resistance models and that the deployment of Bt toxins and non-Bt refuge crops should be adjusted to favor susceptibility of H. zea to Bt toxins such as Vip3Aa. Finally, maize growers should be incentivized to plant non-Bt structured refuge and have access to hybrids with high-yielding genetic potential at a reasonable price.